Long-range mobile signals mediate seasonal control of shoot growth - Miskolczi, Pál; Singh, Rajesh Kumar; Tylewicz, Szymon; Azeez, Abdul; Maurya, Jay P; Tarkowská, Danuše; Novák, Ondřej; Jonsson, Kristoffer; Bhalerao, Rishikesh P (Proceedings of the National Academy of Sciences of the United States of America, 2019)
In perennial plants, seasonal shifts provide cues that control adaptive growth patterns of the shoot apex. However, where these seasonal cues are sensed and communicated to the shoot apex remains unknown. We demonstrate that systemic signals from leaves play key roles in seasonal control of shoot growth in model tree hybrid aspen. Grafting experiments reveal that the tree ortholog of Arabidopsis flowering time regulator FLOWERING LOCUS T (FT) and the plant hormone gibberellic acid (GA) systemically convey seasonal cues to the shoot apex. GA (unlike FT) also acts locally in shoot apex, downstream of FT in seasonal growth control. At the shoot apex, antagonistic factors-LAP1, a target of FT and the FT antagonist TERMINAL FLOWER 1 (TFL1)-act locally to promote and suppress seasonal growth, respectively. These data reveal seasonal changes perceived in leaves that are communicated to the shoot apex by systemic signals that, in concert with locally acting components, control adaptive growth patterns.
Keywords: hybrid aspen; Seasons; systemic signal; Chimera; Arabidopsis Proteins; photoperiodic; výhonky rostlin; gibereliny; Gibberellins; signální transdukce; roční období; fyziologie rostlin; Signal Transduction; proteiny huseníčku; FLOWERING LOCUS T; Plant Physiological Phenomena; gibberellic acid; chiméra; Arabidopsis; regulátory růstu rostlin; Photoperiod; Plant Shoots; Plant Growth Regulators; fotoperioda